Analysis of the relationship between axial length, optic disc morphology, and regional variations in retinal vessel density in young adults with healthy eyes - Chen, Yanhui; Rong, Hua; Liu, Yuling; Gao, Huijuan; Sun, Ziwen; Dang, Weiyu; Lu, Kunpeng; Mi, Baoyue; Li, Jing; Wei, Ruihua (Frontiers in Medicine, 2024)
Purpose To investigate the relationship between optic disc morphology, axial length, and regional distribution of retinal vessels in healthy eyes of young adults. Methods Nine hundred and two healthy eyes were enrolled in this university-based, cross-sectional study. Spectral-domain optical coherence tomography angiography was used to measure the parapapillary retinal vessel density. We automated the process of calculating optic disc tilt and rotation by using a program written in Python. Relationships between optic disc rotation, optic disc tilt, parapapillary vessel density, and other ocular parameters were analyzed using regression models. Results As axial length increased, optic disc morphology became more tilted and rotated inferiorly. The superficial vessel density (SVD) and radial peripapillary capillary density (RPCD) gradually decreased in all regions except for the temporal quadrant. Increased temporal SVD (OR [95% CI] = 1.081 [1.039, 1.124], p < 0.001), reduced nasal SVD (OR [95% CI] = 0.898 [0.861, 0.937], p < 0.01), and short relative lens position (OR [95% CI] = 0.126 [0.032, 0.495], p = 0.003) were significantly associated with the presence of a tilted optic disc. Inferior disc rotation was associated with decreased superior deep vessel density (DVD) and increased inferior DVD and temporal DVD after adjusting for sex and axial length. Conclusion The tilted and rotated optic discs were associated with the distribution of SVD and DVD, respectively. We should fully consider the influence of optic disc morphology on parapapillary vessel density in eyes with myopia.